Assessment of the knowledge of canalis sinuosus amongst dentists and dental students: An online-based cross-sectional study - Lopes-Santos, Gabriela [UNESP]; Salzedas, Leda Maria Pescinini [UNESP]; Bernabé, Daniel Galera [UNESP]; Ikuta, Carla Renata Sanomiya [UNESP]; Miyahara, Glauco Issamu [UNESP]; Tjioe, Kellen Cristine [UNESP] (Wiley, 2021)
Introduction: Canalis sinuosus (CS) is a neurovascular canal that corresponds to a small branch of the infraorbital canal. This study aimed at assessing the knowledge and detection performance of CS amongst dentists and dental students. Materials and Methods: Four-hundred and five dentists and dental students answered a questionnaire with three parts: 1. Socio-demographical; 2. Clinical cases with cone- beam computed tomography (CBCT) sections showing CS and 3. Previous knowledge about CS. The chi-squared test and Spearman's correlation test were used to compare results as appropriate. p-values below.05 were considered statistically significant. Results: Most participants did not identify CS in any CBCT. There was an association between the number of correct answers and dental specialties. Most individuals had not learned about CS previously. There was an association between past knowledge of CS and gender, highest academic degree, working environment, dental specialty and number of correct answers but not with age or experience in Dentistry. Conclusion: This study suggests that most dentists are not aware about CS and do not know how to diagnose it. Previous knowledge about CS positively influenced its identification in CBCT.
Keywords: assessment methods; canalis sinuosus; cone-beam computed tomography; oral health education; oral surgery